If I Leave Here Tomorrow: An Option View of Migration When Labor Market Quality Declines. (12th December 2017) - Gardner, John; Hendrickson, Joshua R.
Abstract : In this article, we provide a framework for determining when it is optimal to move when labor market opportunities are declining. We model the decision to migrate as akin to owning a financial option in which the exercise price is the fixed cost of moving. We show that a higher fixed cost associated with moving and a higher standard deviation of the quality of the labor market reduce the incentive to migrate. We then empirically examine whether the standard deviation of indicators of labor market quality reduce the likelihood of migration. Our findings strongly support this hypothesis, and imply that for the relatively mobile population of high‐skilled workers the counterfactual outmigration rates that would obtain if future labor‐market quality were known with certainty are more than twice observed rates.